1993
DOI: 10.1093/eurheartj/14.5.669
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancy between systolic and diastolic dysfunction of the left ventricle in patients with Duchenne muscular dystrophy

Abstract: To assess the systolic and diastolic dysfunction of the left ventricle (LV) in relation to age and the severity of impairment in Duchenne muscular dystrophy (DMD), we performed M-mode, two-dimensional and pulsed-wave Doppler echocardiography in 45 male subjects with DMD aged 8 to 25 years and in 40 age-matched healthy controls. Systolic dysfunction started in the first decade of life, with some patients showing severe systolic dysfunction in their early teens. This dysfunction, however, did not always depend o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…There were insignificant A wave changes of diastolic mitral valve flow, expressed in A-vmax and A-tvi, respectively. Similar findings were reported by Takenaka et al [34]. Thus far there is no explanation for this behavior.…”
Section: Discussionsupporting
confidence: 90%
“…There were insignificant A wave changes of diastolic mitral valve flow, expressed in A-vmax and A-tvi, respectively. Similar findings were reported by Takenaka et al [34]. Thus far there is no explanation for this behavior.…”
Section: Discussionsupporting
confidence: 90%
“…Severe systolic dysfunction was found in single patients already at their early teens. Diastolic dysfunction was not observed, resulting in the conclusion that DMD patients predominantly develop progressive left ventricular systolic dysfunction [72]. In a study on 23 DMD patients, 5 patients demonstrated atrophic heart, defined as decreasing LVEDD over years [73].…”
Section: Duchenne Muscular Dystrophymentioning
confidence: 99%
“…Classical ECG abnormalities at the subclinical stage are sinus tachycardia, tall R waves in V1, increased R/S ratio in V1, deep Q waves in I, aVL, V5–V6, II, III and aVF and increased QT dispersion. ECG abnormalities predict the cardiac pathology [72]. Echocardiographically, there may be regional wall motion abnormalities and systolic dysfunction, starting in the 1st decade of life.…”
Section: Duchenne Muscular Dystrophymentioning
confidence: 99%
“…Takenaka et al [20] found significant decrease in EF values in MD patients. Also Farah et al [3] showed significant decrease in both EF and FS values.…”
Section: Discussionmentioning
confidence: 93%